Nebulized in-line endotracheal dornase alfa and albuterol administered to mechanically ventilated COVID-19 patients: a case series - Andrew G. Weber; Alice S. Chau; Mikala Egeblad; Betsy J. Barnes; Tobias Janowitz (BMC, 2020)
Abstract Background Mechanically ventilated patients with COVID-19 have a mortality of 24-53%, in part due to distal mucopurulent secretions interfering with ventilation. DNA from neutrophil extracellular traps (NETs) contribute to the viscosity of mucopurulent secretions and NETs are found in the serum of COVID-19 patients. Dornase alfa is recombinant human DNase 1 and is used to digest DNA in mucoid sputum. Here, we report a single-center case series where dornase alfa was co-administered with albuterol through an in-line nebulizer system. Methods Demographic and clinical data were collected from the electronic medical records of five mechanically ventilated patients with COVID-19-including three requiring veno-venous extracorporeal membrane oxygenation-treated with nebulized in-line endotracheal dornase alfa and albuterol, between March 31 and April 24, 2020. Data on tolerability and response were analyzed. Results The fraction of inspired oxygen requirements was reduced for all five patients after initiating dornase alfa administration. All patients were successfully extubated, discharged from hospital and remain alive. No drug-associated toxicities were identified. Conclusions Results suggest that dornase alfa will be well-tolerated by patients with severe COVID-19. Clinical trials are required to formally test the dosing, safety, and efficacy of dornase alfa in COVID-19, and several have been recently registered.